An ultra-thin miniature loop heat pipe cooler for mobile electronics. (25th October 2016) - Zhou, Guohui; Li, Ji; Lv, Lucang
Highlights: A 1.2 mm thick miniature loop heat pipe was developed. The mLHP can manage a wide range of heat loads at natural convection. A minimum mLHP thermal resistance of 0.111 °C/W was achieved at 11 W. The proposed mLHP is a promising solution for cooling mobile electronics. Abstract: In this paper, we present a miniature loop heat pipe (mLHP) employing a 1.2 mm thick flat evaporator and a vapor line, liquid line and condenser with a 1.0 mm thickness. The mLHP employs an internal wick structure fabricated of sintered fine copper mesh, comprised of a primary wick structure in the evaporator to provide the driving force for circulating the working fluid, and a secondary wick inside the liquid line to promote the flow of condensed working fluid back to the evaporator. All tests were conducted under air natural convection at an ambient temperature of 24 ± 1 °C. The proposed mLHP demonstrated stable start-up behavior at a low heat load of 2 W in the horizontal orientation with an evaporator temperature of 43.9 °C and efficiently dissipates a maximum heat load of 12 W without dry-out occurring. A minimum mLHP thermal resistance of 0.111 °C/W was achieved at a heat load of 11 W in a gravity favorable operation mode, at which the evaporator temperature was about 97.2 °C. In addition, an analytical analysis was conducted, and the devised equation could be used to evaluate the performance of the mLHP.